Post-COVID-19 myocardium and coronary involvement in a young patient: differential diagnosis and comprehensive treatment - O. V. Blagova; V. A. Bryukhanov; M. B. Kislova; V. A. Yumasheva; M. S. Gaeva; D. Kh. Ainetdinova; N. V. Gagarina; E. A. Kogan (Кардиоваскулярная терапия и профилактика, 2024)
The state of the heart after a coronavirus disease 2019 (COVID-19, coronavirus disease 2019) is very diverse and in some cases requires a complex differential diagnosis. We described a 35-year-old smoking male patient who, by the end of the first month after COVID-19, developed left ventricular dysfunction with decrease in ejection fraction to 25-30% and persistent left bundle branch block (LBBB). Echocardiography also detected local contractility disorders. A significant increase in blood anticardiac antibody titers was noted. Myocardial biopsy revealed active lymphocytic myocarditis, coronavirus ribonucleic acid, while coronary angiography revealed extensive stenosis of the anterior interventricular artery. On the first day after balloon angioplasty and stenting, the disappearance of LBBB block was noted with the appearance of deep negative T waves in the precordial leads, which did not allow ruling out a previous myocardial infarction. As a result of treatment of heart failure and steroid therapy, the structural and functional cardiac parameters and the electrocardiography were completely normalized by the end of the second year of treatment. Only a transient LBBB remained at high loads. Cardiac computed tomography after 2 years showed no delayed contrast agent accumulation in the myocardium, and coronary stenosis up to 30%.The mechanisms of complex myocardial and coronary damage (including the role of coronaritis in the atherosclerosis progression) after COVID-19 are discussed.